Esthetic Microprostheses for Anterior Teeth: Clinical Rationale for Selecting the Restoration Design - Sergey, Ashrafov Davud; Afrail, Aliyev Mammad Suad (American Journal of Biology and Natural Sciences, 2026)
Microprosthetic restoration of anterior teeth is a widely used approach in contemporary aesthetic dentistry. Veneers allow correction of discoloration, shape abnormalities, and surface defects of hard dental tissues with minimal invasive intervention. Throughout life, teeth are exposed to various organic and inorganic pigments. Some remain on the enamel surface, causing superficial staining, while others penetrate enamel and dentin, leading to intrinsic discoloration. Modern veneers are considered an effective solution for aesthetic rehabilitation of the anterior dentition, providing high esthetic integration and functional stability. Proper clinical protocol ensures minimal impact on periodontal tissues. Contemporary ceramic materials and zirconia dioxide are commonly used for veneer fabrication. Dental ceramics are glass-based materials characterized by smooth surface texture, color stability, and biocompatibility. Zirconia dioxide is a high-strength material widely used in prosthetic dentistry for more than a decade due to its favorable mechanical and esthetic properties.